Wairangi - Trego-Hall, Tiana (Te Kaharoa, 2020)
Cicadas sing under the hot summer sun; a gentle breeze cool the nikau trees along the riverbank uplifting an aroma of freshly cut grass. Waipoua Campgrounds never looked so vivacious. Hearing the call of nature, two cousins strip off their t-shirts and dive into the awa.